Mass Transfer of Oxygen and Power Consumption with Highly Viscous Liquid in Gas-Liquid Agitated Vessel - Haruki Furukawa; Kento Matsumoto; Yoshihito Kato; Masataka Kamiya; Masahiro Haitsuka; Noboru Kamei (Journal of Chemical Engineering Research Updates, 2017)
The gas-liquid mass transfer volumetric coefficient (KLa) and power consumption under aeration are important parameters for designing gas-liquid agitated vessel. In this work, KLawas calculated by measuring the dissolved oxygen concentration and the mixing power consumption was calculated by measuringshaft torque in the aerated mixing vessel equipped with several types of large paddle impeller. It was found that the aerated mixing power consumption with the large paddle impellers did not decrease largely, because the large cavity was not formed behind the impeller blade. Then, KLa of large paddle impellers used was correlated with a modified equation of Sato et al. The intercept of Sato’s equation was correlated with the viscosity of CMC aqueous solution. KLaof large paddle impellers is estimated by using the modified Sato’s equation over a wide range of viscosity.